1) 0,8 * 5 - 5,6 = 4 - 5,6 = - 1,6
2) 5 * (- 6) - 7 * (- 5) = - 30 - (- 35) = - 30 + 35 = 5
3) а = 9 (см); b = 9 + х (см); Р = (а + b) * 2 = (9 + 9 + х) * 2 = 2х + 36
4) х (т) - до обеда; х - 5 (т) - после обеда; х + х - 5 = 2х - 5 (т) - всего привезли;
5) 7b - 3x + b + 2x = 8b - x
15t + (12 - 11t) = 15t + 12 - 11t = 4t + 12 = 4 * (t + 3)
3a + 5b - (2a - b) = 3a + 5b - 2a + b = 6b + a
9h + 9(2d - h) = 9h + 18d - 9h = 18d
6) 2у - (у - (у - (у + 7))) = у - 7
2у - (у - ( у - у - 7)) =
2у - (у - у + у + 7) =
2у - у + у - у - 7 =
3у - 2у - 7 =
у - 7
3/(2^(2 - x²) -1)² - 4/(2^(2- x²) -1) + 1 ≥ 0 ;
замена : t = 2^(2-x²) -1
3 / t² - 4 / t +1 ≥ 0 ;
(t² - 4t +3) / t² ≥ 0
для квадратного трехчлена t² - 4t +3 t₁=1 корень: 1² - 4*1+3 = 1- 4+3 =0.
t₂ =3/t₁=3/1=1 (или t₂ =4 -1=3)
* * * наконец можно и решить уравнение t² - 4t +3=0 * * *
(t² - 4t +3) / t² ≥ 0 ⇔ (t -1)(t - 3) / t² ≥ 0 .
+ + - +
Объяснение:a)
{ 2^(2-x²) -1 ≤ 1 ; 2^(2-x²) -1 ≠ 0 .⇔ { 2^(2-x²) ≤ 2 ; 2^(2-x²) ≠ 1 . ⇔
{ 2^(2-x²) ≤ 2¹ ; 2^(2-x²) ≠ 2⁰.⇔ {2-x² ≤ 1 ; 2 - x² ≠ 0.⇔{ x² -1 ≥ 0 ; x² ≠ 2⇔
{ (x+1)(x-1) ≥ 0 ; x ≠ ±√2 . ⇒ x∈ ( -∞ ; -√2 ) ∪ (-√2 ; -1] ∪ [1 ; √2) U (√2 ; ∞) .
b)
2^(2-x²) -1 ≥ 3 ⇔ 2^(2-x²) ≥ 4 ⇔2^(2-x²) ≥ 2² ⇔2- x² ≥ 2 ⇔ x² ≤ 0 ⇒ x=0.
ответ: x∈ ( -∞ ; -√2 ) ∪ (-√2 ; -1] ∪ { 0} ∪ [1 ; √2) U (√2 ; ∞) .